1983
DOI: 10.1139/x83-071
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism relating cambial electrical resistance to periodic growth rate of balsam fir

Abstract: Cambial electrical resistance (CER) and periodic growth rate (PGR) of canopy balsam fir (Abiesbalsamea L.) trees were determined on 26 sites in Maine, New Hampshire, and Vermont, U.S.A., varying in level of spruce budworm defoliation. Determinations of water and potassium concentrations were made of the bark, wood, and vascular cambial zone (VCZ). Low CER was associated with high PGR and vice versa. A decline in PGR on all 26 sites was detected during early 1970's to late 1970's. It was not associated with, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Changes in electric resistance were therefore used to monitor rehydration of tree trunks. Resistance to AC of <1 kHz (or impedance) between electrodes in tree trunks varies with the amount and ion content of cell sap released by cells wounded during electrode insertion and thus reflects abundance and water status of living cells in stem tissues (Blanchard et al 1983). For avocado (Persea) and spruce (Picea), electric resistance, expressed as percent of the speciesspecific maximum, was found to be highly correlated with ~leaf (Dixon et al 1978).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in electric resistance were therefore used to monitor rehydration of tree trunks. Resistance to AC of <1 kHz (or impedance) between electrodes in tree trunks varies with the amount and ion content of cell sap released by cells wounded during electrode insertion and thus reflects abundance and water status of living cells in stem tissues (Blanchard et al 1983). For avocado (Persea) and spruce (Picea), electric resistance, expressed as percent of the speciesspecific maximum, was found to be highly correlated with ~leaf (Dixon et al 1978).…”
Section: Methodsmentioning
confidence: 99%
“…CER measurements in balsam fir showed that trees with a CER of 9 kΩ or less grew three times faster than trees with a CER of 13 kΩ (Davis et al 1980). Subsequent work with balsam fir indicated that CER was related to the width or number of vascular cambial cells in the current growth ring (Smith et al 1984) and the concentration of mobile ions, principally K in the cambial zone (Blanchard et al 1983) CER also reflected the beneficial effects of liming on foliar-and soil-element content. Lower CER occurred in trees with higher foliar concentrations of Ca and Mg and lower levels of Al and Mn growing in the limed plots.…”
Section: Cambial Electrical Resistancementioning
confidence: 99%
“…Electric resistance to AC of <1 kHz (or impedance) between electrodes in tree trunks varies with the amount and ion content of cell sap released by cells wounded during electrode insertion and hence with abundance and water status of living cells in stem tissues (Blanchard et al 1983). For avocado (Persea) and spruce (Picea), electric resistance, expressed as percent of the species-specific maximum, was found to be highly correlated with ~Jleaf (Dixon et al 1978).…”
Section: Measurement Of Tree Water Statusmentioning
confidence: 99%